Cingulate neglect in humans: Disruption of contralesional reward learning in right brain damage. (January 2015) - Lecce, Francesca; Rotondaro, Francesca; Bonnì, Sonia; Carlesimo, Augusto; Thiebaut de Schotten, Michel; Tomaiuolo, Francesco; Doricchi, Fabrizio
Abstract: Motivational valence plays a key role in orienting spatial attention. Nonetheless, clinical documentation and understanding of motivationally based deficits of spatial orienting in the human is limited. Here in a series of one group-study and two single-case studies, we have examined right brain damaged patients (RBD) with and without left spatial neglect in a spatial reward-learning task, in which the motivational valence of the left contralesional and the right ipsilesional space was contrasted. In each trial two visual boxes were presented, one to the left and one to the right of central fixation. In one session monetary rewards were released more frequently in the box on the left side (75% of trials) whereas in another session they were released more frequently on the right side. In each trial patients were required to: 1) point to each one of the two boxes; 2) choose one of the boxes for obtaining monetary reward; 3) report explicitly the position of reward and whether this position matched or not the original choice. Despite defective spontaneous allocation of attention toward the contralesional space, RBD patients with left spatial neglect showed preserved contralesional reward learning, i.e., comparable to ipsilesional learning and to reward learning displayed by patients without neglect. A notable exception in the group of neglect patients was L.R., who showed no sign of contralesional reward learning in a series of 120 consecutive trials despite being able of reaching learning criterion in only 20 trials in the ipsilesional space. L.R. suffered a cortical-subcortical brain damage affecting the anterior components of the parietal-frontal attentional network and, compared with all other neglect and non-neglect patients, had additional lesion involvement of the medial anterior cingulate cortex (ACC) and of the adjacent sectors of the corpus callosum. In contrast to his lateralized motivational learning deficit, L.R. had no lateral bias in the early phases of attentional processing as he suffered no contralesional visual or auditory extinction on double simultaneous tachistoscopic and dichotic stimulation and detected, with no exception, single contralesional visual and auditory stimuli. In a separate study, we were able to compare L.R. with another RBD patient, G.P., who had a selective lesion in the right ACC, in the adjacent callosal connections and the medial-basal prefrontal cortex. G.P. had no contralesional neglect and displayed normal reward learning both in the left and right side of space. These findings show that contralesional reward learning is generally preserved in RBD patients with left spatial neglect and that this can be exploited in rehabilitation protocols. Contralesional reward learning is severely disrupted in neglect patients when an additional lesion of the ACC is present: however, as demonstrated by the comparison between L.R. and G.P. cases, selective unilateral lesion of the right ACC does not produce motivational neglect for the contralesional space.